Efektifitas Pengelolaan Perpustakaan - Suyanik, Suyanik; Riyanto, Yatim; Soedjarwo, Soedjarwo (Jurnal Ilmiah Mandala Education (JIME), 2021)
The aim of the effectivenes of library mnajemen is to foster a culture of literacy, icrease the capacity of residents and the environment, as a fun and child-friendly learning park, maintain the continuity of learning by presentinga variety of reading books of accommodating various reading strategies. While the method used to callect observasional data. The ttechnique of sorting and analizing data in this activity uses quantitative research method were collected, grouped then presented in the form of quantitative, description. The data/resuts obtained (actual output) are divided by the target value.